Brain-Computer Interfaces in Assistive Technologies: A Bibliometric Review - Judijanto, Loso; Vandika, Arnes Yuli; Toalib, Ramli (Eastasouth Institute, 2025)
This study presents a comprehensive bibliometric review of scholarly literature on Brain-Computer Interfaces (BCIs) in assistive technologies, aiming to map research trends, intellectual structure, and collaborative patterns from 2000 to 2024. Using data retrieved from the Scopus database and analyzed through VOSviewer, this review identifies key contributors, institutional affiliations, and country-level collaborations. Results show a steady increase in publication output, with a sharp surge in 2024, indicating growing academic and clinical interest in BCI-assisted systems. The United States, Germany, and India emerge as the most productive countries, while institutions such as Eberhard Karls Universität Tübingen and Harvard Medical School lead in scholarly output. Author co-authorship analysis reveals influential figures and collaborative hubs, particularly in Europe and North America. Thematic clustering of keywords uncovers major research domains, including neurophysiological signal processing, machine learning applications, robotic control systems, and user-focused communication aids. Overlay and density visualizations suggest an evolution from foundational EEG-based research to more sophisticated, AI-enhanced and ethically grounded assistive technologies. This review provides a data-driven understanding of the field’s development and highlights future directions toward more inclusive, adaptive, and scalable BCI solutions for individuals with disabilities.